Factors Influencing the Marketing Activities of Textile Enterprises in Uzbekistan (International Journal of Scientific Trends, 2025)
This article examines the factors affecting the marketing activities of Uzbek textile enterprises. In recent years, as a result of working with buyers around the world, diversifying the range of goods, developing new markets to increase sales volumes, and attracting foreign investments, the capacity of commodity markets has also been changing dramatically. In this regard, scientific research is being conducted to develop strategic marketing when entering foreign markets, develop marketing strategies that are adaptable to market conditions, and improve marketing activities at enterprises.